2012
DOI: 10.1095/biolreprod.111.098095
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Fatty Acid Transport and Metabolism by Maternal Obesity in the Human Full-Term Placenta1

Abstract: Knowledge of the consequences of maternal obesity in human placental fatty acids (FA) transport and metabolism is limited. Animal studies suggest that placental uptake of maternal FA is altered by maternal overnutrition. We hypothesized that high maternal body mass index (BMI) affects human placental FA transport by modifying expression of key transporters. Full-term placentas were obtained by vaginal delivery from normal weight (BMI, 18.5-24.9 kg/m(2)) and obese (BMI > 30 kg/m(2)) women. Blood samples were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
122
3
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(148 citation statements)
references
References 69 publications
20
122
3
3
Order By: Relevance
“…Additionally, obese women have an increased risk of giving birth to a very low birth weight baby (McDonald et al, 2010). Finally, no alteration of fetal weight by maternal obesity was reported in another study, but it was associated with a decrease in placental efficiency (Dubé et al, 2012).Biometry of the feto-placental unit has been obtained from different animal models of high maternal weight or obesity. Offspring from obese ewes increased their weight at mid-gestation whereas placentome weight was not altered (Zhu et al, 2009).…”
mentioning
confidence: 99%
“…Additionally, obese women have an increased risk of giving birth to a very low birth weight baby (McDonald et al, 2010). Finally, no alteration of fetal weight by maternal obesity was reported in another study, but it was associated with a decrease in placental efficiency (Dubé et al, 2012).Biometry of the feto-placental unit has been obtained from different animal models of high maternal weight or obesity. Offspring from obese ewes increased their weight at mid-gestation whereas placentome weight was not altered (Zhu et al, 2009).…”
mentioning
confidence: 99%
“…82 In addition, studies in human full-term placentas showed that maternal obesity impacts placental fatty acid uptake and could therefore modify the fetus metabolism and the child's predisposition to develop diseases later in life. 83 Maternal obesity leads to a lipotoxic placental environment that is associated with decreased regulators of angiogenesis and increased markers of inflammation and oxidative stress. 84 This environment via in utero programming may trigger adaptive pathways which ultimately result in increased percentage of body fat and propensity for future obesity in the offspring of obese women.…”
mentioning
confidence: 99%
“…Placentas of obese women demonstrate decreased sodium-dependent neutral amino acid transporter (System A) expression (34) and, at least in vitro, IL-1β inhibited insulin-stimulated System A amino acid uptake in human placental trophoblast cells (35). Obese women show placental dysregulation of redox balance (36), decreased fatty acid transport, and increased placental lipoprotein lipase activity which could be responsible for placental triglycertides accumulation (37), although this contrasts to placenta-derived data from animal models studying diet-induced maternal obesity (see below).…”
Section: Impacts Of Maternal Obesity: Overview Of Epidemiologic Studiesmentioning
confidence: 99%